Identifying and Controlling the Order Parameter for Ultrafast Photoinduced Phase Transitions in Thermosalient Materials - Ghasemlou, Saba; Li, Xinyue; Galimberti, Daria R.; Nikitin, Timur; FAUSTO, RUI; Xu, Jialiang; Holleman, Steven; Rasing, Theo; Cuppen, Herma M. (National Academy of Sciences, 2024)
The drastic shape deformation that accompanies the structural phase transition in thermosalient materials offers great potential for their applications as actuators and sensors. The microscopic origin of this fascinating effect has so far remained obscure, while for technological applications, it is important to learn how to drive transitions from one phase to another. Here, we present a combined computational and experimental study, in which we have successfully identified the order parameter for the thermosalient phase transition in the molecular crystal 2,7-di([1,1’-biphenyl]-4-yl)-fluorenone. Molecular dynamics simulations reveal that the transition barrier vanishes at the transition temperature. The simulations further show that two low-frequency vibrational-librational modes are directly related to the order parameter that describes this phase transition, which is supported by experimental Raman spectroscopy studies. By applying a computational THz pulse with the proper frequency and amplitude we predict that we can photoinduce this phase transition on a picosecond timescale. © 2024 the Author(s).
Keywords: Molecular Dynamics; Molecular Machines; Phase Transitions; THz Spectroscopy